Odpowiedzi

2009-11-27T18:44:04+01:00
A)(x+4)²
b)(2a-3b)²
c) (4x+5)(4x-5)
d)(0,5m-0,1)²
e)(1/2*xy+1)²
f)(0,4m-0,2n)(0,4m+0,2n)
g)(7-5/6*y²)(7+5/6*y²)
h)(9x²+5y)²
1 5 1
Najlepsza Odpowiedź!
2009-11-27T20:47:39+01:00
A)
x²+8x+16= (x +4)²
b)
4a²-12ab+9b²= (2a - 3b)²
c)
16x²-25= (4x - 5)(4x + 5)
d)
0,25m²-0,1m+0,01 = (0,05m - 0,1)²
e)
1/4 x²y²+xy+1= (1/2xy +1)²
f)
0,16 m²-0,04n²= (0,04m - 0,02n)(0,04m + 0,02n)
g)
49- 25/36y⁴= (7 - 5/6y²)(7 + 5/6y²)
h)
81x⁴+90x²y+25y²= (9x² + 5y)²
2009-11-27T22:49:16+01:00
A) x²+8x+16=(x+4)² ze wzoru (a+b)²=a²+2ab+b²
b) 4a²-12ab+9b²=(2a-3b)² ze wzoru (a-b)²=a²-2ab+b²
c) 16x²-25=(4x+5)(4x-5) ze wzoru a²-b²=(a+b)(a-b)
d) 0,25m²-0,1m+0,01 =(0,5m-0,1)² ze wzoru (a-b)²=a²-2ab+b²
e) 1/4 x²y²+xy+1=(1/2*xy+1)²ze wzoru (a+b)²=a²+2ab+b²
f) 0,16 m²-0,04n²=(0,4m-0,2n)(0,4m+0,2n) ze wzoru a²-b²=(a+b)(a-b)
g) 49- 25/36y⁴=(7-5/6*y²)(7+5/6*y²) ze wzoru a²-b²=(a+b)(a-b)
h) 81x⁴+90x²y+25y²=(9x²+5y)ze wzoru (a+b)²=a²+2ab+b²